h.hofstede (h.hofstede@hogeland.nl)

       
1. 2x - 3 - 4x = -2 4x + 8
-2x - 3 = -8x + 8
-2x = -8x + 11
6x = 11
x = 11/6
   
       
2. -2 - 3 p 3 + p = 4p 2 + 1
-2 - 9p + p = 8p + 1
-2 - 8p = 8p + 1
-8p = 8p + 3
-16p = 3
p = -3/16
   
       
3. -2 - 5 - 6a = 4a 2 - 4
-2 - 5 - 6a = 8a - 4
-7 - 6a = 8a - 4
-6a = 8a + 3
-14a = 3
a = -3/14
   
       
4. 10 - 6 a : 2 = -2 - 2a - 3
10 - 3a = -5 - 2a
-3a = -15 - 2a
-a = -15
a = 15
   
       
5. 2 + 3 3 - x = -3 2 x + 8
2 + 9 - x = -6x + 8
11 - x = -6x + 8
-x = -6x - 3
5x = -3
x = -3/5
   
       
6. -2 - x - 2 - x = 2x -3 + 4
-2 - x - 2 - x = -6x + 4
-4 - 2x = -6x + 4
-2x = -6x + 8
4x = 8
x = 2
   
       
7. -3 -y + 4 = 2 y - 6 : 3
3y + 4 = 2y - 2
3y = 2y - 6
y = -6
   
       
8. p - 7 + p - 2 p = p  
-7 = p
   
       
9. 3p 2 -2  - 2p = -p  + 26
-12p - 2p = -p + 26
-14p = -p + 26
-13p = 26
p = -2
   
       
10. 2c 4 6 - 2 = 5 - c 4 - 6
48c - 2 = -1 - 4c
48c = 1 - 4c
52c = 1
c = 1/52
   
       
       
       

h.hofstede (h.hofstede@hogeland.nl)